Clinical Profile and Echocardiographic Evaluation of COPD Patients Admitted in a Tertiary Care Hospital (Journal of Medicine, 2024)
Introduction: Chronic obstructive pulmonary disease (COPD) ranks as the fourth leading cause of global mortality, with anticipated increases in prevalence and mortality in the future. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) highlights the importance of considering COPD diagnosis in patients with relevant symptoms or risk factors, confirmed through spirometry. While COPD is preventable and treatable, it often presents with significant extra-pulmonary effects, particularly cardiac manifestations. Echocardiography offers a rapid, noninvasive method to assess these cardiac complications. Objective: This study aimed to investigate the clinical profiles and echocardiographic changes in COPD patients and their correlation with disease severity. Method: Conducted as an observational cross-sectional study, the research took place in the indoor departments of Medicine and Respiratory Medicine at Sir Salimullah Medical College & Mitford Hospital, Dhaka, between May 25th, 2017, and November 24th, 2017; enrolling 105 diagnosed COPD patients aged e”18 years. Data collection involved a structured questionnaire covering socio-demographic details, risk behavior, and respiratory complaints. Physical examinations, spirometry, and echocardiography were conducted for diagnosis, severity grading, and cardiac evaluation, respectively. Statistical analysis employed SPSS software (version-22), presenting results through frequency, percentage, tables, graphs, and figures. Result: The study population was predominantly male (88.6%) with a mean age of 64.1 years. Most patients (94.2%) were smokers with a mean pack-year history of 22.03. All patients presented with cough and shortness of breath, and 88.5% had wheezing. Spirometry revealed moderate COPD in 40% of patients, with a distribution across all severity grades. Echocardiography showed abnormalities in 52.4% of patients, with tricuspid regurgitation, pulmonary hypertension, and right ventricular dilatation being the most frequent findings. A significant correlation was observed between C OPD severity and the presence of these echocardiographic abnormalities. Conclusion: Clinical examination unveiled common respiratory findings, while echocardiography demonstrated diverse cardiac manifestations in COPD patients. A significant proportion of patients exhibited normal findings on X-ray and echocardiography. The study highlights the prevalence of moderate COPD severity and the association between very severe COPD and specific cardiac complications, emphasizing the importance of comprehensive assessment and management strategies for COPD patients.J MEDICINE 2024; 25: 115-120